Transitions to Adulthood and Generational Change in Portugal - Ramos, Vasco (2018)
Much of the research on contemporary youth in Western societies has shown that transitions to adulthood are being postponed, protracted, and becoming more complex (i.e., less likely to follow a predictable and “orderly” sequence as in earlier generations). Extended schooling periods, changes in the labor market and challenges to obtaining autonomous housing are some of the top drivers for such change. Demographers interpret such developments as a sign of a second demographic transition, whereas sociologists stress that they are a consequence of the broader process of social individualization, by which individuals are assuming an increasingly central role in the organization of their lives. While in younger cohorts the evidence base is strong concerning transitions to adulthood, in some national contexts comparisons with the past rely on impressionistic accounts or to easily assume that some social, economic, and cultural factors were present. Drawing on data from the “Family Trajectories and Social Networks: The life course in an intergenerational perspective” research project, this paper re-examines the transitions to adulthood of three Portuguese cohorts (born in 1935–1940, 1950–1955 and 1970–1975), namely in what concerns their timing, duration, and sequence. This is achieved by looking at their life-calendars across different domains (namely family and intimate relations, school, and work). Analysis of the results allows us to discuss critically to what extent current transitions to adulthood are different and to assess cohort heterogeneity according to class and gender. Additionally, it enables us to frame discussions on generational and structural change more adequately in Portugal.